The effect of selection and use of technology education teaching methods and techniques - (:unkn) unknown (SILA SCIENCE, 2012)
This study examined the effect of various variables on the instructional, teaching strategies, methods, and the selection and use of technical terms used by teachers working in vocational high schools. The research presents a screening model. The study investigated teachers in vocational high schools in Istanbul during 2009-2010. The sample included 14 vocational high schools serving 372 randomly selected teachers from the most diverse sectors of the Anatolian side of Istanbul during the 2009-2010 academic years. This study analyzed teachers' use of educational technologies for statistical analysis methods and techniques used during the lessons and the impact of their selection and use. The SPSS statistical program analyzed the data. The study assessed the frequency, percentage, arithmetic mean, and standard deviation to analyze results and employed the t-test, ANOVA, and multivariate linear regression analysis. According to these results, vocational and technical education teachers often use graduate level technology and technology-supported teaching strategies. Regression analysis of the frequency of the use of technology-supported instructional strategies, tools, and methods of operation is effective.
Keywords: Instructional technology; Technology assisted teaching strategies; Teaching methods and techniques; TEACHERS; STUDENTS; REFORM